2011
DOI: 10.3233/jad-2011-110011
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Galanin Protects Mouse Hippocampal Neurons Against Amyloid Toxicity in vitro via Activation of Galanin Receptor-2

Abstract: Expression of the neuropeptide galanin is known to be upregulated in the brain of patients with Alzheimer’s disease (AD). We and others have shown that galanin plays a neuroprotective role in a number of excitotoxic injury paradigms, mediated by activation of the second galanin receptor subtype (GAL2). In the present study, we investigated whether galanin/GAL2 plays a similar protective role against amyloid-β(Aβ) toxicity. Here we report that galanin or the GAL2/3-specific peptide agonist Gal2-11, both equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…In vitro, administration of galanin or galanin (2-11) may rescue the neurotoxicity induced by Aβ (25-35) or Aβ (1-42) in rat primary cultured hippocampal neurons (Cheng and Yu, 2010;Elliott-Hunt et al, 2011). Similar results were also demonstrated using cultured human primary neurons (Cui et al, 2010).…”
Section: Galanin and Alzheimer's Diseasesupporting
confidence: 80%
See 3 more Smart Citations
“…In vitro, administration of galanin or galanin (2-11) may rescue the neurotoxicity induced by Aβ (25-35) or Aβ (1-42) in rat primary cultured hippocampal neurons (Cheng and Yu, 2010;Elliott-Hunt et al, 2011). Similar results were also demonstrated using cultured human primary neurons (Cui et al, 2010).…”
Section: Galanin and Alzheimer's Diseasesupporting
confidence: 80%
“…These findings indicate that the actived GalR2/3 may involved in the protective effects against hippocampal Aβ aggregation(Cheng and Yu, 2010;Cui et al, 2010;Elliott-Hunt et al, 2011;Pirondi et al, 2010).Further studies demonstrated the ability of galanin to improve spatial memory impairment and to decrease hippocampal Aβ levels via activation of GalR2(Elliott-Hunt et al, 2007Li et al, 2013). On one hand, the levels of galanin and GalR2 mRNA were increased significantly in the hippocampus after Aβ administration, whereas GalR1 mRNA and protein levels were not changed(Li et al, 2013).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…It has been shown that GAL2R can protect the hippocampus from neuronal damage and regulate the neurite outgrowth from adult sensory neurons in a PKC-dependent manner [22,23]. GAL2R can also influence neuronal survival and seizure-induced neurogenesis in the dentate gyrus [24].…”
Section: Introductionmentioning
confidence: 99%